Zastosowanie trójwymiarowej ultrasonografii w okulistyce - Wilczyński, Michał; Suprunowicz, Irena (Klinika Oczna / Acta Ophthalmologica Polonica, 2007)
Development of ophthalmology in recent years is connected with perfecting diagnostic methods and equipment. Ultrasound examination, because of its good availability, repetitiveness and non-invasiveness has become a commonly used method in ophthalmic diagnosis. Three-dimensional ultrasound (3DUS), also called three-dimensional ultrasound tomography, is an advanced method based on digital analysis of series of two-dimensional images. This technique is especially useful in ocular oncology, vitreoretinal pathologies and ocular trauma. Authors present selected cases visualised using 3DUS technique and discuss its advantages in comparison with traditional two-dimensional scans.